Relationships between parental behaviour, peer influence, self-control and aggressive behaviour among adolescents in Selangor, Malaysia - Pung, Pit Wam (2015)
Aggressive behaviour might lead to negative consequences for both of the victim and aggressor. Thus, the current study was conducted to determine the relationships between parental behaviour (paternal and maternal involvement, paternal and maternal positive parenting, paternal and maternal poor monitoring, paternal and maternal inconsistent discipline, paternal and maternal corporal punishment), peer influence, self-control and aggressive behaviour among adolescents in Selangor, Malaysia. This study also examined the mediating role of self-control on the relationship between parental behaviour and peer influence with adolescents’ aggressive behaviour. This is a quantitative non-experimental study utilizing correlational research design. The respondents of the study consisted of 413 adolescents from 12 selected secondary schools. They were 186 males and 227 females who were identified by Multistage Cluster Sampling Technique. Instruments used for data collection were Alabama Parenting Questionnaire (Shelton, Frick & Wootton, 1996), Peer Delinquency Scale (Loeber, Farrington, Stouthamer-Loeber, & Van Kammen, 1998), The Aggression Questionnaire (Buss & Perry, 1992) and SelfControl Scale (Grasmick, Tittle, Bursik, & Arneklev, 1993). Descriptive, Pearson correlation test and multiple regression analysis were used in data analysis. Pearson correlation analysis showed that the parental behaviour (paternal involvement, paternal positive parenting, paternal and maternal poor monitoring, paternal and maternal inconsistent discipline, paternal and maternal corporal punishment), peer influence and self-control were significantly correlated with aggressive behaviour. In addition, the parental behaviour (paternal involvement, paternal and maternal poor monitoring, paternal and maternal inconsistent discipline, paternal and maternal corporal punishment) and peer influence were significantly associated with self-control. Multiple regression analysis showed that self-control, paternal corporal punishment, maternal educational level, paternal poor monitoring, paternal positive parenting, peer influence and respondent’s gender predict adolescents’ aggressive behaviour. Self-control served as the strongest predictor in adolescents’ aggressive behaviour. The present study also found that selfcontrol fully mediated the relationship between paternal involvement, maternal corporal punishment, paternal inconsistent discipline, and peer influence with aggressive behaviour. Besides, self-control also partially mediated the relationship between paternal and maternal poor monitoring, paternal corporal punishment, and maternal inconsistent discipline with aggressive behaviour. The findings of the present study highlighted the importance of parental behaviour, peer influence and self-control in terms of its contribution in aggressive behaviour among adolescents in Selangor, Malaysia. Parent should practise positive parenting in order to prevent adolescents from involving in aggressive behaviour. The issue of adolescents’ aggressive behaviour also can be overcome by helping adolescents to develop self-control and be more assertive in refusing negative influence from peers.